Description of the process of tunneling Q signaling in Private telecommunication networks - Svrzić, Slađan; Miličević, Zoran; Perišić, Zoran (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The article should specify the network signaling type Q-SIG, which is standardized especially for implementation in digital telecommunication networks of integrated services (ISDN), emphasizing the possibility of its further application in the Private Telecommunications Network of Integrated Services of the Serbian Armed Forces (PISN of SAF), i.e. in the Private Automatic Telephone Network of the Serbian Armed Forces (PATN of SAF). Methods: An analysis of the existing standards was performed: ECMA-355 and ECMA-336 and a synthesis of the possibilities of their application in the PATN of SAF. Results: The procedure for the application of Q-SIG is processed in a situation when the peripheral parts of the PISN of SAF, which operate on the principle of transmission and circuit switching by TDM (Time Division Multiplexing), are connected via a central Core network with the IP (Internet Protocol), which operates on the principle of packet transmission and switching with the SIP (Session Initiation Protocol). A method of the application of the tunneling of encapsulated Q-SIG messages through the IP network, defined by ECMA-355 Standard, has been developed. The necessary functions for mapping the transmission of tunneled signaling messages Q-SIG and mapping voice (and other audio) information to media streams during VoIP (Voice over IP) communication through that network, which are defined by ECMA-336 Standard, are described. Conclusion: The application of ECMA-355 and ECMA-336 Standards is a new solution in the PATN of SAF with the use of the IP network to connect the IP PINX using the Q-SIG tunneling procedures and mapping functions for their transmission and transmission of audio signals. This then opens up a whole range of new possibilities that, with the growth of the Core network and their application, will rapidly contribute to the creation of a broad Telecommunication information system backbone for the implementation of real-time multimedia communications and the transition to Unified Communications (UC).